2017
DOI: 10.1177/1010428317705758
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Dalton’s lymphoma–induced angiogenesis by melatonin

Abstract: For tumor to grow beyond 1-2 mm size, tumor recruits new blood vessels referred as angiogenesis; therefore, targeting angiogenesis can be a promising strategy to suppress cancer progression. In this study, in order to develop a good angiogenesis model, we investigated effect of Dalton's lymphoma on angiogenesis and further monitored the role of melatonin on regulation of angiogenesis. To evaluate angiogenesis, endothelial cells were isolated from main thoracic aorta and cultured in vitro in the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Melatonin, alone or in combination with vinorelbine, also increased TIMP3 expression, an inhibitor of angiogenesis that limits vessel density close to tumors and reduces tumor growth 67 . Recently, it has been described that melatonin reduces Dalton's lymphoma-induced angiogenesis by increasing TIMP3 expression 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, alone or in combination with vinorelbine, also increased TIMP3 expression, an inhibitor of angiogenesis that limits vessel density close to tumors and reduces tumor growth 67 . Recently, it has been described that melatonin reduces Dalton's lymphoma-induced angiogenesis by increasing TIMP3 expression 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin inhibited the proliferation, migration, and sprouting of the tertiary branching in chorioallantoic membrane and mesentery of Dalton's lymphomabearing mice. In addition, the indolamine was capable to restore anti-angiogenic related genes, such as tissue inhibitor of metalloproteases 3 (TIMP-3), reducing, at the same time, the expression of VEGF, VEGFR, and FGF [86]. In glioblastoma stem-like cells, melatonin inhibited the pro-angiogenic EZH2-NOTCHI signaling pathway [87].…”
Section: Melatonin Antiangiogenic Actions and Cancermentioning
confidence: 99%
“…were defined for Dalton lymphoma, renal adenocarcinoma, colon cancer cells, and ovarian carcinoma cells (K. J. Kim et al, 2013;Kumari, Rawat, Kumari, & Shrivastava, 2017;Park et al, 2010;Zonta et al, 2017). In the human gastric cancer cells it has been shown that melatonin beside to VEGF and HIF-1 can reduce angiogenesis by suppression of nuclear receptor RZR/RORγ (R.-X.…”
Section: Melatonin Effects On Angiogenesismentioning
confidence: 99%